Study of incidence, microbiological profile of nosocomial infections in pediatric intensive care unit of tertiary care center - Malagi, Naushad Ali N.; Sushma, Uppalapati; Thangavelu, S.; Shanthi, S.; Ramchandran, P.; Indumathi; Ravichandran, C.; Gangawati, Sujay P.; Lahari, Darla Sri Sai (International Journal of Contemporary Pediatrics, 2023)
Background: Prevalence of nosocomial infections in pediatric intensive care unit (PICU) ranges between from 6-26%. Increased use of broad-spectrum antibiotics, urinary and central venous catheterization and endotracheal intubation put patients at an increased risk of affecting with nosocomial infections in pediatric patients. Methods: A hospital based prospective study was carried out on 725 patients aged between 1 month and 12 years admitted in PICU of Al-Ameen medical college hospital, Bijapur, Karnataka, India and institute of child health and hospital for children, Madras medical college, Chennai, Tamil Nadu, India from 15-09-2020 to 15-08-2022. All patients who were admitted with fever or developed fever in first 48 hours of life were excluded from the study. The data obtained in the course of study was analyzed by appropriate statistical methods. Results: Out of 725 pediatric admissions, the incidence of nosocomial infection in the present was found to be 108 (14.8%). Concerning the type of infection, the commonest reported types were central-line associated bloodstream infection (CABI) 59 (54.6%) and ventilator-associated infection (VAI) 52 (48.1%), followed by bloodstream infection 45 (41.6%), catheter associated urinary tract infection (CA-UTI) 38 (35.1%) and urinary tract infection (UTI) 30 (27.7%) respectively. Conclusions: The incidence of nosocomial infection was 14.8%. The central line associated blood stream infection was the predominant cause of nosocomial infection. This information can help decision makers establish preventive strategies and implement effective and reliable plans.